Pengungkapan Emisi Karbon: Studi pada Perusahaan Manufaktur di Indonesia - Widiawati, Pipit; Hidayati, Cholis (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2024)
Carbon emission disclosure is a diclosure to assess an organization’s carbon emissions and set targets for reduction. This study aimed to analyze and provide empirical evidence about the impact of firm size, profitability, growth, and environmental performance toward carbon emission disclosure of manufacturing companies in Indonesia. The method that was used to measure the extent of carbon emission disclosure adopted the checklist that was developed based on the information request sheet provided by Carbon Disclosure Project. This research applied purposive sampling method to obtain 15 manufacturing company that listed in Indonesia Stock Exchange (BEI) during 2015-2017. Research data is a secondary data derived from company’s annual and sustainability reports and the hypothesis is tested using multiple regression analysis. The results of this study indicate that firm size have a significant effect on the extent of carbon emission disclosure, however the other factors, such as profitability, growth, and environmental performance have no significant effect to the extent of carbon emission disclosure.